Exploring the Influence of Blended Learning Method in English Recount Text Writing for Senior High School Students - Anak Agung Istri Rita Santi Kusuma; Santosa, Made Hery; Myartawan, I Putu Ngurah Wage (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2020)
This paper aims to explore the influence of blended learning method on the teaching of English recount text writing and examine students’ perceptions toward the implementation of the method. The design of the study was a mixed-method research designs. The data were collected by using a pre-test, post-test, and an open-ended interview. The quantitative data were analyzed using independent samples t-test, while qualitative data obtained from interviewing students were transcribed, categorized, and interpreted using interactive model analysis. The quantitative data analysis showed there was a significant effect of the blended learning method towards students' English recount text writing with a large effect size (1.03). From the interviews, it was found that the students gave positive responses to the implementation of blended learning methods in teaching writing of recount text. It can be concluded that blended learning is an effective method for teaching writing recount text for senior high school. Other researchers are expected to expand the research variable and explore this method's implementation on different English skills.